Potential Impact of Geomagnetic Field in Transcranial Magnetic Stimulation for the Treatment of Neurodegenerative Diseases - Chae, Kwon-Seok; Kim, Yong-Hwan (Frontiers in Human Neuroscience, 2017)
Throughout the long history of various therapeutic trials of transcranial magnetic stimulation (TMS), some TMS protocols have been reported to be clearly effective in the treatment of neurodegenerative diseases. Despite promising results from repetitive TMS (rTMS) using low frequency electromagnetic fields (EMFs) for neurodegenerative diseases, the low reproducibility has hampered the clinical applications of rTMS. Here, based on the notion of radical pair mechanism explaining magnetoreception in living organisms, we propose a new perspective that rTMS with controlled geomagnetic field (rTMS-GMF) can be an efficient and reproducible therapeutic approach for neurodegenerative diseases. In addition, combined consideration of imprinted GMF and/or EMFs in patients’ earlier life may augment the potential efficacy of the rTMS-GMF. The investigation of this approach is intriguing and may have a high impact on the technical suitability and clinical application of the rTMS-GMF in the near future.